Politically Equal But Still Underrepresented: Women And Local Democratic Politics In Indonesia - Sobari, Wawan (Penerbit Universiti Sains Malaysia (USM Press), 2016)
This research challenges the relevance of a change towards liberal democracy for gender equality. In particular, it connects the political logic of the survival and failure of incumbents in the direct election for local leaders (pilkada) with the acceptance of gender related considerations in local policies and women preferences in voting. By carrying out comparative assessments concerning the pilkada in four rural and urban districts in East Java, the study reveals that local democracy does not provide incentives which encourage the incumbents who run in re-election bids to promote better gendered policies during their terms in office due to women's ignorance in voting. Female voters were less critical in reviewing the incumbents' performance. Women were too busy receiving tangible policy outputs; they paid inadequate attention to the importance of strategic gender interests. Consequently, incumbents who perform better in reducing gender disparity often lose their posts. Worse, during local democratic contests, women were marginalised by the practices of male-dominated informal politics amongst the incumbents, informal actors and partisan bureaucrats. Also, the pilkada is not an easy race for women's candidacy, as the regulations do not affirm women and political parties hinge on pragmatic considerations that favour male candidates as having a better chance of winning in election. Moreover, this study challenges the arguments of decentralisation policy that have led to the negligence of local government concerning a gender-mainstreaming agenda. In fact, the decentralisation regulatory regime overwhelmingly controlled by the national government has restricted local governments from better addressing gender strategic needs. The national authority strictly determines local expenditure items, which do not incorporate gender mainstreaming approaches in local budgeting.